KONVERSI ENERGI PEMANGGANG IKAN DENGAN PARA-PARA SISTEM BERTINGKAT - I Made Parsa (LPPM, 2011)
This action research program is aimed at: (1). Giving a course on roasting a kakap fish (Lates Calcarifer) through a working process of a fish roaster apparatus with multi-storied racks. (2). Giving services and demonstration on how to operate kakap fish roasting apparatus and the like, which are appropriate and correct and its maintenance. The method of this action research program uses: instruction, demonstration and evaluation in the use fish roasting apparatus with multi-storied racks, which has been given to Ulam Segara Food Industry in Kelurahan Pasir Panjang, Kupang. The results of this action research program are: (1). the workers of fresh fish food can efficiently fulfill the order of roasted fish consumers from an even and continuous roasting process. (2). The workers of snacks can roast fish, able to process fish into various fish foods/snacks (pepes, sate, rica-rica etc.) evenly in short time, where before the introduction of this apparatus 3 fishes were grated in 15 minutes, but since the operation of this apparatus 10 fishes can be processed in 15 minutes. Key Word: Fish Roasting, Apparatus, Multi-storied Racks